The communication clinic : 99 proven cures for the most common business mistakes - Pachter, Barbara; Cowie, Denise (McGraw-Hill, 2017)
The Communication Clinic is a comprehensive, commonsense guide to getting the job of your dreams and presenting yourself in the best light through your writing, speaking, body language, and overall appearance. In no time, you'll begin recognizing the subtle mistakes that are holding you back, and taking steps to overcome them-- BusinessPro website.